Post-Harvest and Sensory Quality Performance of Open Pollinated Cauliflower Cultivars for Mid-season at Dang District of Nepal - Basnet, Manoj; Srivastava, Arvind; Mishra, Kalyani; Dahal, Kishor Chandra (Nepalese Horticulture, 2023)
The study was conducted at Tulsipur, Dang, Nepal for two years (2021 and 2022 A.D.) to assess the postharvest quality performance of open pollinated (OP) cauliflower curd. Five OP cauliflower cultivars viz. Kathmandu Local, Khumal Jyapu, Agheni, Terai-1 and Terai-2 (seed sourced from Nepal Agriculture Research Council, Khumaltar, Lalitpur) were replicated four times in Randomized Complete Block Design. Freshly harvested curds from respective plots were considered in postharvest and sensory study. Maximum curd dry matter (15.91%) and Vitamin C content (37.94 mg/100 gm) was recorded in Khumal Jyapu whereas, maximum leaf dry matter (12.53%) and TSS (7.1830Brix) were recorded in Aghani. The color score (8.913) and overall appearance score (7.908) were maximum in Khumal Jyapu. The curd compactness score (7.475) and overall acceptance score (8.133) were recorded maximum in Aghani. The lowest physiological loss in curd weight with jacket leaves (8.193%) was recorded in Khumal Jyapu after 3 days after harvesting (DAH) whereas; the lowest physiological loss in curd weight recorded in Aghani were 13.47%, 19.32%% and 25.06% at 5, 7 and 9 DAH respectively. Similarly, the lowest physiological loss in curd weight without jacket leaves recorded in Khumal Jyapu were 10.45%, 14.82%, 22.83% and 29.77% at  3, 5, 7 and 9 DAH respectively. The lowest spoilage losses of curd along with and without jacket leaves recorded in Aghani were 33.27% and 38.77% respectively. Considering the economically important postharvest attributes Khumal Jyapu and Aghani were found to be the suitable mid-season cultivars in Dang condition.